Care and concern in the research process: meeting ethical and epistemological challenges through multiple engagements and dialogue with research subjects - Sörensson, Erika; Kalman, Hildur (Qualitative research : QR, 2018)
By addressing a case of data collection strategies applied in research on Thai migration to the Swedish wild-berry industry, this article argues for how a feminist approach based on care and concern for research subjects both safeguards ethical concerns and promotes good knowing. The data collection procedures were designed in a step-by-step manner, including the research subjects as much as possible at different times and in different ways in an attempt to create preconditions for a more inclusive production of knowledge. In-depth interviews, participant observation, photo documentation and group interviews were used, which facilitated the possibility to understand the content and meanings of wild-berry picking from the workers’ points of view. Through prolonged contact, including repeated encounters and dialogue with research subjects, in-depth knowledge was produced concerning Thai migrations to Sweden, as migration was set in relation to the migrants’ life courses and living conditions.